Systematic review of frameworks used to conceptualise health pathways of individuals diagnosed with cardiovascular diseases - Dina Balabanova; Benjamin Palafox; Alicia Renedo; Maureen L Seguin; Avanti Rangnekar (BMJ Global Health)
The treatment of cardiovascular disease (CVD) is managed inadequately globally. Theoretically informed frameworks have the potential to account for the multiple elements which constitute the CVD patient pathway, and capture their inter-relationships and processes of change. However, a review and critique of such frameworks is currently lacking. This systematic review aims to identify and critically assess frameworks of access to and utilisation of care which capture the pathways of patients diagnosed with one or more CVDs. The specific objectives are to (1) review how existing frameworks have been used and adapted to capture CVD patient pathways and (2) draw on elements of Strong Structuration Theory to critically appraise them, in terms of their ability to capture the dynamics of the patient journey and the factors that influence it. Five bibliographic databases were searched in January 2019. We included qualitative and quantitative studies containing frameworks used to capture the patient pathway of individuals with CVD, encompassing symptoms, diagnosis, treatment and long-term management. Data on patient behaviour and structural factors were interpreted according to elements of Strong Structuration Theory to assess frameworks on their ability to capture a holistic patient journey. The search yielded 15 articles. The majority were quantitative and all focused on management of CVDs, primarily hypertension. Commonly used frameworks included the common-sense self-regulation model, transtheoretical model and theory of planned behaviour. A critique drawing on elements of Strong Structuration Theory revealed these frameworks narrowly focused on patient attributes (patient beliefs/attitudes) and resulting patient action, but neglected external structures that interacted with these to produce particular outcomes, which results in an individualistic and linear view of the patient pathway. We suggest that a framework informed by Strong Structuration Theory is sufficiently flexible to examine the patient pathway, while avoiding a strict linear view facilitated by other frameworks.